MARKETING ANALYSIS OF ARWOOD IN LOMBOK ISLAND - Eka Nurminda Dewi Mandalika (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2022)
This study aims to determine the marketing channel and the efficiency level of marketing of gaharu on Lombok Island. This research was conducted in four regions: West Lombok Regency, North Lombok Regency, Central Lombok Regency, and Mataram City. The respondents consisted of four people: three district-level collectors and one exporter. Determining marketing agency respondents is done using the "Snowball Sampling" method. The analysis tool used is profit analysis of marketing institutions and analysis of marketing efficiency. The results of this study indicate that there are three marketing channels for Lombok Island agarwood. The profits of each marketing agency for the Lombok Island agarwood from November to December 2012 amounted to Rp. 2,125,000 per kilogram for Regency collectors and Rp. 364,400,000 per kilogram for agarwood exporters. Looking at the great potential of the agarwood commodity from Lombok Island, further research is needed to determine the development of the marketing of agarwood on Lombok Island.